2020
DOI: 10.1111/tpj.14847
|View full text |Cite
|
Sign up to set email alerts
|

Sl‐lncRNA15492 interacts with Sl‐miR482a and affects Solanum lycopersicum immunity against Phytophthora infestans

Abstract: Summary Long non‐coding RNAs (lncRNAs) are involved in the resistance of plants to infection by pathogens via interactions with microRNAs (miRNAs). Long non‐coding RNAs are cleaved by miRNAs to produce phased small interfering RNAs (phasiRNAs), which, as competing endogenous RNAs (ceRNAs), function as decoys for mature miRNAs, thus inhibiting their expression, and contain pre‐miRNA sequences to produce mature miRNAs. However, whether lncRNAs and miRNAs mediate other molecular mechanisms during plant resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 63 publications
0
38
0
Order By: Relevance
“…How these MIRNA genes lose their miRNA biogenesis ability remains unclear. Long noncoding RNAs (lncRNAs) have been reported to inhibit the expression of mature-Sly-miR482a in Solanum lycopersicum 39 . In the present study, we found that miRNA processing of MIR398 family genes is disrupted by their cis -NATs transcribed from coding genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How these MIRNA genes lose their miRNA biogenesis ability remains unclear. Long noncoding RNAs (lncRNAs) have been reported to inhibit the expression of mature-Sly-miR482a in Solanum lycopersicum 39 . In the present study, we found that miRNA processing of MIR398 family genes is disrupted by their cis -NATs transcribed from coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…Most documented cis -NATs correspond to protein-coding genes, with only a few cis -NATs of noncoding MIRNA genes having been reported 36 , 38 , 39 . Our previous study first identified a subset of cis -NATs corresponding to MIRNA genes in Brassica rapa 16 , including BrpMIR398b and BrpMIR398c .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some lncRNAs interact with microRNAs (miRNAs), serving as miRNA precursors or competing endogenous RNAs (ceRNAs) to serve as decoys for specific miRNAs, thus protecting the target mRNAs from repression [29][30][31][32] . In recent years, several studies have indicated that lncRNAs play important roles in various biological processes in plants, including roles in organ development, nutrient metabolism, male sterility, and plant immunity [33][34][35][36][37] . In particular, lncRNAs are considered essential regulators of the response to biotic and abiotic stresses in plants 30,[38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…The ISR processes involving several regulatory components have been well explored (Van Wees et al, 2008;Banks et al, 2012;Timmermann et al, 2019), but the roles of lncRNAs in the PGPRinduced ISR responses remain elusive so far. It is increasingly evidenced that lncRNAs can act as positive regulators of plant innate immunity: pathogen infection induces the expression of several miRNAs to suppress plant defense responses; meanwhile, a healthy plant is able to activate the lncRNA-mediated defense responses for decoying these negative regulators of defense systems (Jing et al, 2019;Hou et al, 2020;Jiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%